View Single Post
Old 1st December 2012, 12:10 AM
HatCat's Avatar
HatCat HatCat is offline
Alpha Tester
Project Supporter
Senior Member
Join Date: Feb 2007
Location: In my hat.
Posts: 16,236

x^2 + bx + c == [x + sqrt(c)]^2
x^2 + bx + c == x^2 + 2*x*sqrt(c) + c
bx = 2x*sqrt(c)
x != 0 // simplifies uselessly to c == sqrt(c)
b = 2*sqrt(c)
2*sqrt(c) = b
4c = b^2
c = 0.25 * b^2

Add one-fourth the square of b to a binomial of the form (x^2 + bx) to transform it into a perfect square trinomial.

(Damn, I need to get back to that Sine of One Degree thing, I left all those 60+ sheets of ink-stained paper filled with my work on that back at DE xD)
Reply With Quote